A smartphone-colorimetric dual-mode diagnosis method for breast cancer detection of BRCA-1 gene base on silver plated substrate and catalytic hairpin assembly amplification - Zan Yu; Wenxin Liu; Lei Wang (Journal of Nanobiotechnology)
Abstract Breast cancer is the most prevalent malignancy among women worldwide. With rapid societal development, there has been a consistent increase in breast cancer incidence rates annually, accompanied by a progressively younger age of onset. Consequently, there is an urgent need to develop a rapid, sensitive, and highly specific approach for the identification of BRCA-1. In this study, we successfully devised a heterogeneous system based on G-quadruplex DNAzyme for label-free and enzyme-free visual detection of BRCA-1. Moreover, the distinctive G-quadruplex (G4) DNAzyme ensures precise and accurate detection through enzyme-free amplification, colorimetric detection, and catalytic hairpin assembly mechanisms. The utilization of this heterogeneous system effectively minimizes background interference while exhibiting exceptional sensitivity and accuracy with an impressive detection limit as low as 0.6 pM. Furthermore, real sample analysis yielded an area under the ROC curve value of 0.9825 which demonstrates its robust performance for early screening purposes when integrated with smartphone-assisted analysis, thus showcasing its potential for widespread application in early breast cancer diagnosis.